Performance measurement of management system standards using the balanced scorecard - Jan Kopia; Andreas Kompalla; Melanie Buchmüller; Bastian Heinemann (Amfiteatru Economic Journal, 2017)
Management system standards (MSS), such as ISO standards, TQM, etc. are widely -used standards adopted by millions of organizations worldwide. It is still an unclear question whether these standards are beneficial for an organization, besides the fact that they might be required or expected by law or customers. The question, whether MSS increase the efficiency, the output, or the performance of an organization is still discussed in scientific research. One reason might be that performance measurement itself is not fully understood or in constant development ranging from pure financial evaluations over intellectual capital rating to calculating of levels of environmental, social or economic expectations known as the Trible Bottom Line. The Balanced Scorecard is one possible solution for performance measurement on a strategic and operational level and therefore useful for the measurement of the influence of MSS within organizations. This study summarized current research in the field of performance measurement in the context of MSS and IMS and the use of BSC and quantitatively and qualitatively tests the usefulness of BSC in measuring the effect of MSSs using the Execution Premium. It was found that BSC is often used, that an average number of companies integrate their measurement initiatives of their MSSs into the BSC-process, and that a high integration of MSS into the BSC improves the organizational performance. This research is useful for researchers and practitioners in order to understand the benefits of the usage of the BSC in the context of MSS or Integrated Management Systems.
Keywords: M10; L10; L15; L25; 330; performance management; balanced scorecard; strategy maps; management system standards; integrated management systems; executive premium